Leader's Toxicity at Workplace: How Leader's Decadence Affect Employees? A Pakistani Perspective. (May 2022) - Qureshi, Muhammad Azeem; Ramish, Muhammad Sufyan; Ansari, Junaid; Bashir, Muhammad Adnan
Several studies have found adverse effects of abusive leadership on employees and organizations in the recent past. However, the cultural norms in Pakistan demand an abusive leadership approach. Pakistani culture is high in power distance, abuse of power is a norm, and people are accustomed to autocracy. Since most of the studies addressing the negative effects of abusive leadership were conducted in the west, it is necessary to examine whether abusive leadership is an effective leadership approach in the cultures that experience high power distance. There is a paucity of literature addressing the issue in question. In addition, existing literature does not explain how abusive leaders affect employees' attitudes and behaviors with clarity. This research makes an ontological contribution and discusses the philosophical origins of abusive leadership theory. Furthermore, this research draws the inference using the groundings of conservation of resource theory, leader-member exchange theory, and aggression displaced theory to propose that abusive leaders deteriorate employees' quality of working life experience. Employees with poor working-life experience are more likely to be involved in counterproductive work behavior, planning to leave the organization, and are less likely to show organizational citizenship behavior. Dyadic data were collected from 474 respondents based on purposive sampling technique from private sector organizations in Pakistan. Results of structural equation modeling using AMOS v23 supported all the proposed hypotheses. Results imply that the moral content of leadership requires special attention, and abusive leadership is not an appropriate leadership approach because of its adverse effects on employees' attitudes and behaviors.